Chemical Constituents from the Twigs of Decaneuropsis vagans (Asteraceae) and Its Chemotaxonomic Study - Anuruk Chailungka (Science Faculty of Chiang Mai University, 2019)
The first phytochemical investigation of the twigs of Decaneuropsis vagans (DC.) H. Rob. & Skvarla. resulted in the isolation of six known compounds, including lupeol palmitate (1), lupeol acetate (2), eugenol (3), macelignan (4) and a mixture of  -sitosterol (5) and stigmasterol (6). Their structures were characterized by various spectroscopic methods and comparison with the data reported in the literature. Compounds 1-6 were isolated from this species for the first time and compound 4 was firstly found in the Asteraceae family.